La representación del erotismo en la novela La tía Tula de Miguel de Unamuno - Loma Salas, Cristina Elizabeth (2023)
The work of Miguel de Unamuno (Bilbao, September 29, 1864-Salamanca, December 31, 1936) represents the social and religious ideology of Spain at the beginning of the twentieth century, taking women as the primary agent and their incidence in different imaginaries. The present research identifies, analyzes, and characterizes eroticism in the novel La tía Tula, written in 1907 and published in 1921 by Renacimiento and considered one of the hundred best novels of the twentieth century. The objective is to understand the interactions of eroticism within a literary work to recognize the feminine role in the epochal social fabrics. This research has a qualitative approach and a descriptive nature. It comprised the following phases: situational diagnosis, exploration of the research problem, review of bibliographic sources, prioritization of information of interest, analysis and discussion of the results, and formulation of conclusions and recommendations. Through the documentary review and the assumption of the hermeneutic method and the content analysis technique, the thematic and conceptual spheres of the representations of eroticism in the work in question were characterized. The researcher concluded that the expressions of eroticism in La tía Tula by Miguel de Unamuno, far from conforming to an explicit system or imaginary, assume instead a confiscation, urged by the historical-social-cultural precepts connected to femininity in the Spain of the second half of the twentieth century.